Dietary Pulses as an Accessible Means to Improve the Gut Microbiome, Inflammation, and Appetite Control in Individuals with Obesity - St John, Hannah (Université d'Ottawa / University of Ottawa, 2022)
Interest in the gut bacterial community residing in the human intestine, otherwise known as the gut microbiota, has exploded in recent years. The gut microbiome has been linked to chronic diseases such as obesity, suggesting interventions that target the microbiome may be useful in treating obesity and its complications. Dietary pulses (e.g., common beans) are composed of nutrients and compounds that possess the potential to modulate the gut bacteria composition and function which can in turn improve appetite regulation and chronic inflammation in obesity. This review summarizes the current state of knowledge regarding the connection between the gut microbiome and obesity, appetite regulation, and systemic and adipose tissue inflammation. More specifically, it highlights the efficacy of interventions employing dietary common beans as a means to improve appetite regulation and inflammation in obesity in both rodent models and in humans. Collectively, results presented and discussed herein provide insight on the gaps in knowledge necessary for a comprehensive understanding of the potential of beans as a treatment for obesity while highlighting what further research is required to gain this understanding.
Keywords: Gut microbiota; Inflammation; Appetite; Dietary pulses